In Vivo Photoelectrochemical Analysis - Li Li; Yueru Zhao; Cong Pan; Wenjie Ma; Ping Yu (Chemosensors)
Microelectrode-based photoelectrochemical (PEC) technology is a novel and rapidly developing analytical method for the in vivo probing of neurochemical events in the brain, which is distinguished by its low background noise and high detection sensitivity. This mini-review focuses on recent advances in in vivo PEC biosensors. We classify the key characteristics of PEC technology and elucidate its underlying principles. Furthermore, newly developed PEC neurochemical sensing methods for detecting various substances, including SO2, antibiotics, metal ions, neurotransmitters, and thioalcohols, as well as cells are discussed. Finally, this review concludes with a comprehensive summary and perspectives on the emerging opportunities and challenges facing this field.